2022
DOI: 10.1021/acs.jpca.1c09648
|View full text |Cite
|
Sign up to set email alerts
|

ReaxFF Force Field Development for Gas-Phase hBN Nanostructure Synthesis

Abstract: Two-dimensional (2D) hexagonal boron nitride materials are isomorphs of carbon nanomaterials and hold promise for electronics applications owing to their unique properties. Despite the recent advances in synthesis, the current production capacity for boron nitride (BN) nanostructures is far behind that for carbon-based nanostructures. Understanding the growth mechanism of BN nanostructures through modeling and experiments is key to improving this situation. In the current work, we present the development of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…For the gas-phase simulations, the box was set at 2.1 nm × 1.1 nm × 6.5 nm, which included 200 BCl 3 and 200 NH 3 . Although ReaxFF MD simulations employ relatively high pressure to accelerate the simulations, the higher pressure does not affect the occurring reactive events. , Therefore, we can expect similar reactive events at normal pressures on a micro- or millisecond scale, even at higher pressures. The initial configuration of the gas molecules was equilibrated by using the energy minimization method.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the gas-phase simulations, the box was set at 2.1 nm × 1.1 nm × 6.5 nm, which included 200 BCl 3 and 200 NH 3 . Although ReaxFF MD simulations employ relatively high pressure to accelerate the simulations, the higher pressure does not affect the occurring reactive events. , Therefore, we can expect similar reactive events at normal pressures on a micro- or millisecond scale, even at higher pressures. The initial configuration of the gas molecules was equilibrated by using the energy minimization method.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Therefore, the force field should capture precursor geometries and chemical reactions between Si/O/H/B/Cl/N atoms for the ALD process simulation. Previously, the B/N/H force field was parametrized by Lele et al in 2022 to model the BN nanostructure formation in the gas phase . We newly introduce the B–Cl bond, B–Cl off-diagonal, and Cl–B–Cl angle in the B/N/H force field as the force field does not include these B–Cl-related descriptions.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Aside from the impact of precursor concentration and temperature, the role of the surface orientation on the graphene growth was also investigated by Lu and Yang [147]. Particularly, for the simulations using naphthalene and fluorene as precursors, Ni (100) and Ni (211) were found to have stronger surface interaction with volatile molecules, leading to the formation of discontinuous carbon networks, whereas Ni (111) surface exhibited moderate surface interaction and was beneficial to the formation of larger graphene nanosheets (figure 4(b)). Chen et al [148] identified the CVD pathway of the CH 4 decomposition and the subsequent evolution from C segments to graphene.…”
Section: Synthesis Techniques 4121 Cvd Growthmentioning
confidence: 99%
“…B/N-2022 [211] Modified B/N-2010 [215] by adding the reaction energies and barriers for B-N species and rings formation in the gas phase chemistry using B2H6/NH3 as precursors. This optimized force field is utilized to model the gas phase chemistry during CVD synthesis process using BN and HBNH as precursors.…”
Section: Reaxff Parameter Setmentioning
confidence: 99%
“…Recent ReaxFF force fields have been validated and extensively applied to modeling carbon materials (Mao et al, 2022;Mao et al, 2020;Kowalik et al, 2019;Rajabpour et al, 2021a;Zhang et al, 2020;Vashisth et al, 2020), 2D materials (Curry et al, 2021;Rajabpour et al, 2021b;Nayir et al, 2020;Nayir et al, 2021a;Nayir et al, 2021b;Ostadhossein et al, 2017;Lele et al, 2022;Mojtabavi et al, 2021;Ganeshan et al, 2020), oxidation kinetics of MXenes (Zhao et al, 2020a;Zhao et al, 2019;Lotfi et al, 2018;Zheng et al, 2021) and multiple other materials.…”
Section: Introductionmentioning
confidence: 99%